The effect of turn residues on the folding and cell‐penetrating activity of β‐hairpin peptides and applications toward protein delivery. Issue 1 (12th June 2019) - Miller, Stephen E.; Schneider, Joel P.
Abstract: Cell‐penetrating peptides (CPPs) are useful tools for the delivery of a wide variety of cargo into cells. Our lab has developed two classes of CPPs based on β‐hairpin sequences, one that folds at the surface of cell membranes and the other that is intrinsically disordered. Although these peptides can effectively deliver different types of cargo, their use in protein delivery has been hindered due to the presence of non‐natural D‐proline within the central turn region of both sequences, which prohibits functionalizing proteins with the CPPs via standard expression protocols. In this work, we describe new CPPs that replace the non‐natural turn region with natural turn motifs amenable to protein expression. We first investigate how these changes within the turn affect various CPP‐related properties in the absence of protein cargo, and then generate protein fusions for intracellular delivery. Abstract :